Photoprotective Cream Containing Brown Seaweed (Sargassum Sp.) Extract: Optimization By Simplex Lattice Design - Endriyatno, Nur Cholis; Nurhidayat, Lina Aliyanti (Sciences of Pharmacy, 2025)
Sunlight containing ultraviolet (UV) rays is harmful to human skin health. Sunscreen is one of the trendy and attractive cosmetics. Brown seaweed extract (Sargassum sp.) has the potential to be developed into a sunscreen product. This study aimed to optimize the formula of a cream containing brown seaweed extract and its in vitro photoprotection. A simplex lattice design approach was used to factor (triethanolamine and stearic acid) and responses (pH, viscosity, adhesiveness, and spreadability). The concentration of variation in stearic acid and triethanolamine affects the parameters of pH response, viscosity, adhesion, and spreadability. The simplex lattice design predicts the optimal formula with stearic acid (17%) and triethanolamine (4%). The verification proved that no significant difference between the predicted and actual results. The in vitro photoprotective evaluation results indicate that the brown seaweed extract cream is categorized as providing high sun protection and serving as a sunblock. Optimization of the brown seaweed extract cream formula using stearic acid and triethanolamine factors has been successfully achieved. The conclusion is that brown seaweed extract cream has the potential to be developed into a sunscreen cosmetic.